Exploring production management and social media strategy mapping in educational institutions - Khairunnisa Devani Aqtus Permana Putri; Melisa Bunga Altamira (Privietlab, 2026)
Information technology continues to evolve, requiring society to adapt quickly. This acceleration has led to digital technology disruption, resulting in massive changes to human life, such as in production, distribution, and advertising in the media. Several educational institutions have used Instagram to connect various elements both inside and outside the campus, one of which is the UI Vocational Education Program on Instagram @vokasi_ui. UI Vocational continues to creatively produce content related to education and entertainment. This study uses a qualitative descriptive approach with field research methods, using observation and document study as data collection methods. Production management and content mapping on the @vokasi_ui Instagram account are carried out through content diversity, consistency of uploads, utilization of Instagram features, and interaction with followers through the stages of planning, organizing, actuating, and controlling.